Noninferiority Clinical Trials: The Good, the Bad, and the Ugly - Lesaffre, Emmanuel (Seminars in Liver Disease, 2018)
For decades, the superiority trial has been the most popular design to assess the efficacy of newly developed drugs in a randomized controlled clinical trial. In a superiority trial, the aim is to show that the new (experimental) treatment is better than the standard treatment or placebo. However, it becomes increasingly difficult to improve the efficacy upon that of existing drugs. For this reason, noninferiority designs have been suggested. In a noninferiority study, one aims to show that the experimental treatment does not lower the efficacy of the standard treatment too much, but this loss of efficacy should be compensated by other better properties. In this article, the design, aims, and properties of the superiority and the noninferiority trial are contrasted and illustrated on recently published studies to treat patients with advanced hepatocellular carcinoma. The author discusses the reasons why noninferiority studies are becoming popular, but also why the results of noninferiority studies may be difficult to interpret and can be easily misused. Since only a few noninferiority studies in hepatocellular cancer have been organized, also examples from other therapeutic areas were taken. Finally, it is indicated how to appreciate the qualities of published noninferiority studies.
Keywords: equivalence trial; noninferiority trial; nonsignificance; superiority trial